2020
DOI: 10.3389/fonc.2020.00231
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Beyond a Waste Metabolite: Metabolic Affairs and Signaling in Malignancy

Abstract: To sustain their high proliferation rates, most cancer cells rely on glycolytic metabolism, with production of lactic acid. For many years, lactate was seen as a metabolic waste of glycolytic metabolism; however, recent evidence has revealed new roles of lactate in the tumor microenvironment, either as metabolic fuel or as a signaling molecule. Lactate plays a key role in the different models of metabolic crosstalk proposed in malignant tumors: among cancer cells displaying complementary metabolic phenotypes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 144 publications
4
87
0
1
Order By: Relevance
“…Thus, in cancer cells, glucose gets converted partly into CO 2 but mostly into lactic acid, consequently resulting in increased levels of lactate outside in the tumor microenvironment. Recent studies have shown that this extracellular lactate participates in promoting cancer cell survival and proliferation by multiple autocrine and paracrine mechanisms via the cell-surface receptor GPR81 (HCAR1 or hydroxycarboxylic acid receptor 1) [ 11 , 12 ]. Another important aspect of the increased rate of glycolysis in cancer cells is the elevated levels of glycolytic intermediates, which can feed into metabolic pathways that provide additional support to cancer cell proliferation.…”
Section: Aerobic Glycolysismentioning
confidence: 99%
“…Thus, in cancer cells, glucose gets converted partly into CO 2 but mostly into lactic acid, consequently resulting in increased levels of lactate outside in the tumor microenvironment. Recent studies have shown that this extracellular lactate participates in promoting cancer cell survival and proliferation by multiple autocrine and paracrine mechanisms via the cell-surface receptor GPR81 (HCAR1 or hydroxycarboxylic acid receptor 1) [ 11 , 12 ]. Another important aspect of the increased rate of glycolysis in cancer cells is the elevated levels of glycolytic intermediates, which can feed into metabolic pathways that provide additional support to cancer cell proliferation.…”
Section: Aerobic Glycolysismentioning
confidence: 99%
“…Increased glucose uptake and metabolism to fuel aerobic glycolysis is also a general feature of mitogenic stimulation under physiological conditions and oncogenic transformation [ Figure 1B and Refs. ( 67 69 )] and is generally referred to as the Warburg effect. Although it was originally assumed that tumor cells upregulate glycolysis even in the presence of oxygen due to defective mitochondria, it is now clear that increased rates of glycolysis allow the redirection of metabolic fluxes toward more efficient biomass production ( 69 , 70 ) in actively proliferating cells and form the molecular basis of using PET scans for tumor detection ( 71 ).…”
Section: Aerobic Glycolysis May Increase Phc Via Nhe1 Activationmentioning
confidence: 99%
“…Lactate, once considered a dead‐end product of glycolysis, is emerging as an essential regulator of multiple biological processes, including tumor metabolism, the immune response, and signal transduction 23,33 . Increased lactate uptake is a characteristic of lung cancer metabolism 5 .…”
Section: Discussionmentioning
confidence: 99%